SISTEM PEMILIHAN UMUM KEPALA DAERAH DALAM PEMILIHAN UMUM DI INDONESIA - Ardin Ardin (Maleo Law Journal, 2019)
Regional Head Election System in General Elections in Indonesia, the settlement of which is initially in the Supreme Court and then moves to the Constitutional Court based on Article 236C of Law Number 12 of 2008. The discussion of this thesis is: First is the objective to find out whether the system Election of Regional Head and Deputy Regional Head in General Elections can give birth democratically. To find out how the Electoral Low system and Electoral Process. To find out how the mechanism of post-conflict local election dispute resolution in Central Sulawesi. The scope of space describes the state of the system of Election of Regional Heads and Deputy Regional Heads in Central Sulawesi, elaborating the Electoral Low and Electoral Process system, elaborating the post-conflict local election dispute resolution system. Keyword: Regional and Electoral Head Electoral System in Elections